The role of fecal microbiota transplantation in type 2 diabetes mellitus treatment - Wang, Huimei; Li, Shuo; Zhang, Luping; Zhang, Nan (Frontiers in Endocrinology, 2024)
In contemporary microbial research, the exploration of interactions between microorganisms and multicellular hosts constitutes a burgeoning field. The gut microbiota is increasingly acknowledged as a pivotal contributor to various disorders within the endocrine system, encompassing conditions such as diabetes and thyroid diseases. A surge in research activities has been witnessed in recent years, elucidating the intricate interplay between the gut microbiota and disorders of the endocrine system. Simultaneously, fecal microbiota transplantation (FMT) has emerged as a focal point, garnering substantial attention in both biomedical and clinical spheres. Research endeavors have uncovered the remarkable therapeutic efficacy of FMT across diverse diseases, with particular emphasis on its application in addressing type 2 diabetes mellitus (T2DM) and associated com-plications. Consequently, this manuscript accentuates the intimate connection between the gut microbiota and disorders within the endocrine system, with a specific focus on exploring the potential of FMT as an intervention in the therapeutic landscape of T2DM and its complications. Furthermore, the article scrutinizes concerns inherent in treatment modalities centered around the gut microbiota, proposing viable solutions to address these issues.